Identification and Spatial Pattern of Kao Bay Bathymetry Based on UNCLOS - Yulius, Yulius; Salim, H L (Forum Geografi, 2015)
Kao Bay is located in the province of North Maluku between Regency of North Halmahera and West Halmahera. The study aims are to identify bay criteria according to UNCLOS and bathymetry based on Nautical Chart. The methods used in this study are the identification of the bay area under UNCLOS and spatial analysis using GIS software. The result shows that Kao Bay has a coast line length of 127.7 km, a mouth bay cover line of 11.1 km, total surface area of Â 964.38 Â km2, and total surface semi-circular bay cover area of 48.4 km2. The total surface area larger than the area of the semicircle bay cover area. It has been full compliance with the criteria required by UNCLOS. Spatial analysis, found that for the depth of water in Kao Bay can be divided into six classes, these are: (1) 0 â 100 meter with area of 964,38 km2, (2) 100 - 200 meter with area of 667.25 km2, (3) 200 - 300 meter with area of 556.95 km2, (4) 300 - 400 meter with area of 376.89 km2, (5) 400 - 500 meter with area of 202.44 km2, (6) 500 - 600 meter with area of 2.22 km2.